Recent Progress in Analytical Method Development and Validation of Dapagliflozin: Review Article (Journal of Pharma Insights and Research, 2025)
Recent advances in analytical methodology for dapagliflozin quantification have highlighted various instrumental approaches crucial for pharmaceutical quality control. Dapagliflozin, a sodium-glucose co-transporter-2 inhibitor, requires precise analytical methods for its determination in pharmaceutical formulations. Multiple validated techniques including UV spectrophotometry, reversed-phase high-performance liquid chromatography (RP-HPLC), and high-performance thin-layer chromatography (HPTLC) have emerged for analyzing dapagliflozin alone and in combination with other antidiabetic agents. UV spectrophotometric methods demonstrate simplicity and cost-effectiveness, utilizing various solvents and detecting wavelengths between 210-280 nm. RP-HPLC methods employ C18 columns with diverse mobile phase compositions, achieving efficient separation with retention times typically under 6 minutes. Method validation parameters encompass linearity, precision, accuracy, specificity, and robustness following International Conference on Harmonisation (ICH) guidelines. Reported linear ranges vary from 5-100 μg/mL for UV methods and 10-250 μg/mL for HPLC methods, with correlation coefficients exceeding 0.99. Recovery studies indicate accuracies between 98-102%, while precision studies show relative standard deviations below 2%. Several stability-indicating assays confirm method selectivity and ability to detect degradation products.